Pinguicula habilii (Lentibulariaceae), a new carnivorous species from South-West Anatolia, Turkey - Yildirim, Hasan; Şenol, Serdar Gökhan; Pi̇rhan, Ademi̇ Fahri̇ (Phytotaxa, 2012)
Pinguicula habilii (Lentibulariaceae), described as a new species of carnivorous plants, is distributed in the province of Muğla in Southwestern Anatolia, Turkey. A full description, diagnostic morphological characters, and detailed photographs of this new species including SEM microphotographs of seed and pollen are given. The new species belongs to the section Cardiophyllum of Pinguicula subgenus Isoloba. It resembles the P. crystallina and P. hirtiflora. It differs from the related species by its heterophyllous growth, leaf shape and peculiar seed coat sculpture. It grows on serpentine rocks at elevations between 100 and 200 m.